(untitled) (Informatica, 2022)
The global health situation due to the SARS-COV-2 pandemic motivated an unprecedented contribution of science and technology from companies and communities all over the world to fight COVID-19. In this paper, we present the impactful role of text mining and data analytics, exposed publicly through IRCAI’s Coronavirus Watch portal. We will discuss the available technology and methodology, as well as the ongoing research based on the collected data.